Thoharoh Dalam Al-Qur’an: (Kajian Tafsir Tahlili Surat Al-Maidah Ayat 6 Tafsir Al-Azhar) - Khairani, Naila; Feby, Novandasabina (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
When someone has reached the age of puberty, they are considered religiously mature and are expected to understand the obligations in Islam, including performing prayers regularly according to the specified times and procedures. One of the important preparations before performing prayer is performing ablution, tayammum, or obligatory bathing. In the study of this verse, it states that purification is one of the valid requirements for performing prayer.